RNA Degradation in Eukaryotic Cells - Tatosyan, K. A.; Ustyantsev, I. G.; Kramerov, D. A. (Molecular biology (New York), 2020)
RNA is a crucial component of every living organism and is necessary for gene expression and its regulation in the cell. Mechanisms of RNA synthesis (especially mRNA synthesis) were a subject of extensive study for a long time. More recently, RNA degradation pathways began to be considered as equally important part of eukaryotic cell metabolism. These pathways have been studied intensely, and ample information accumulated about RNA degradation systems and their role in cell life. It is currently obvious that RNA decay is of no less importance as RNA synthesis and contributes to regulating the RNA level in the cell. The review considers the main RNA degradation enzymes, the decay pathways of various coding and non-coding RNAs, the mechanisms providing RNA quality control in the nucleus and cytoplasm, and certain structural elements responsible for RNA stability or short life in the cell.